Pendidikan Jiwa Menurut Ibnu Qayyim Al Jauziyyah - Hamdani, Arfan; Rohimah, Siti (Lembaga Yasin AlSys, 2026)
Spiritual education is an essential aspect of Islam that is oriented toward holistic personality formation, encompassing spiritual, moral, and intellectual dimensions. Ibn Qayyim al-Jawziyyah places spiritual education (tazkiyatun nafs) at the core of educational success, which is measured not only by intellectual intelligence but also by purity of the soul, steadfastness of faith, and nobility of character. This study aimed to examine the concept of spiritual education according to Ibn Qayyim al-Jawziyyah and its implications for the development of Islamic education. A library research method with a qualitative–descriptive approach was employed through content analysis of Ibn Qayyim’s major works. The findings show that spiritual education is intended to direct human beings toward true servitude to Allah SWT through the processes of tazkiyah and tahliyah, by cultivating a balanced relationship between khauf, raja’, and mahabbah. Spiritual education must be grounded in the Al-Qur’an and the Sunnah and realized through the habituation of righteous deeds and the exemplary conduct of educators. This concept is relevant as a holistic paradigm of Islamic education for shaping a generation that is knowledgeable, faithful, and of noble character.